A Study of ROI Based Sign Language to Text Translation in Real Time Using Deep Learning - Soujanya S.; Ruhaima; Rajashree Nambiar; Sakshi; Shanthika (International Journal of Optical Innovations & Research, 2024)
Since sign language is their primary form of communication, it plays a significant role in the lives of hearing and speech disabled people. However, since not everyone is conversant in sign language, it is challenging for the disabled to interact with others daily. Sign language is made up of a variety of hand gestures that may stand in for a wide range of words and sentiments. The purpose of this study is to develop a trustworthy communication interpretation. Using image processing and Machine learning, this paper translates Indian Sign Language into legible output. So, we convert the sign languages into letters and then to words and to sentences which can be understood easily by the people who do not understand sign languages. So, this translation may be used for everyday communication and can be used to teach different gestures to autonomous systems that use gestures as input.
Keywords: Gesture recognition; MATLAB; a KINECT sensor; hand gesture scan; sign language